2016
DOI: 10.1016/j.yrtph.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Tobacco Heating System 2.2. Part 3: Influence of the tobacco blend on the formation of harmful and potentially harmful constituents of the Tobacco Heating System 2.2 aerosol

Abstract: The Tobacco Heating System (THS2.2), which uses "heat-not-burn" technology, generates an aerosol from tobacco heated to a lower temperature than occurs when smoking a combustible cigarette. The concentrations of harmful and potentially harmful constituents (HPHCs) are significantly lower in THS2.2 mainstream aerosol than in smoke produced by combustible cigarettes. Different tobacco types and 43 tobacco blends were investigated to determine how the blend impacted the overall reductions of HPHCs in the THS2.2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 34 publications
7
58
0
1
Order By: Relevance
“…On the other hand, the concentration of tar in the mainstream smoke of iQOS was half or less than that of the conventional combustion cigarettes. From a comparison with other data reported by Schaller et al, these concentrations were at almost the same level [10]. Next we measured the concentration of CO in the mainstream smoke of iQOS.…”
Section: Concentrations Of Tar Nicotine and Co In Mainstream Smoke Asupporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, the concentration of tar in the mainstream smoke of iQOS was half or less than that of the conventional combustion cigarettes. From a comparison with other data reported by Schaller et al, these concentrations were at almost the same level [10]. Next we measured the concentration of CO in the mainstream smoke of iQOS.…”
Section: Concentrations Of Tar Nicotine and Co In Mainstream Smoke Asupporting
confidence: 67%
“…Although it is low concentration, toxic compounds are definitely included in the mainstream Table 1 [16], so adverse effects of these compounds may easily spread to an unspecified population in the public and in crowded indoor places, such as restaurants via secondhand smoking. Various other hazardous compounds, such as volatile organic compounds (VOCs), are also included in both the particle and gas phases of mainstream smoke of iQOS [10,17]. In consideration of this, we need further chemical evaluation and studies of their health effects in order to support regulation of iQOS in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations of several major carcinogens in cigarette smoke and in VNP vapour were obtained from studies of cigarettes,14 27 28 a prototype HnB device29 and EC products, ranging from early-generation disposables through second-generation clearomisers and cartomisers to third-generation mods and tanks 7 30–37. EC coil resistance and battery voltage were collated where reported.…”
Section: Methodsmentioning
confidence: 99%
“…The tobacco industry has performed multiple studies regarding health consequences of HTP use. The results of in vitro and in vivo studies indicate that HTP aerosols have lower toxicity and no new hazards compared to conventional cigarette smoke [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The results of humanbased studies also suggest that switching from conventional cigarettes to IQOS or glo leads to reductions in exposure to smoke toxicants in a manner comparable to quitting tobacco use [74][75][76][77][78].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 95%
“…Following the manufacturer recommendations, especially proper cleaning of the device after each 20 tobacco sticks seems to be crucial to provide proper thermal regulation and reduce emissions of harmful substances. Most of the research regarding the chemical composition of generated aerosol was carried out on brand new, never used devices [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Independent researchers showed that the use of 1 IQOS tobacco stick left a significant amount of debris, fluid, and fragments of cast-leaf in the device holder [8].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%